Indonesian Student of Arabic Language: Needs and Aspirations | متعلم العربية في إندونيسيا حاجاته وتطلعاته - Wael Aly Sayed (Al-Zahra : Journal for Islamic and Arabic Studies, 2016)
The theme of this research on the reality of an educated Arabic language in Indonesia, and their needs and aspirations, and I try of this research to monitor the most important phenomena related to the learner Indonesian, and enjoyed by the skills and potential, and aspire to the high level makes it no less important than the Arab individual in possession of the corner language, and through my personal experience as a visiting professor of Arab language and literature at the Faculty of Islamic and Arabic Studies at the University of Syarif Hidayatullah State Islamic Jakarta, Indonesia for three months at the first of September to thirty of November 2016.